2009
DOI: 10.1002/dneu.20727
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin as a determinant for altered neurogenesis, neuritogenesis, and synaptogenesis

Abstract: Elevated levels of serum unconjugated bilirubin (UCB) in the first weeks of life may lead to long-term neurologic impairment. We previously reported that an early exposure of developing neurons to UCB, in conditions mimicking moderate to severe neonatal jaundice, leads to neuritic atrophy and cell death. Here, we have further analyzed the effect of UCB on nerve cell differentiation and neuronal development, addressing how UCB may affect the viability of undifferentiated neural precursor cells and their fate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 79 publications
(87 reference statements)
3
26
0
Order By: Relevance
“…In particular, we have previously demonstrated that PCs showed a neurodegenerative phenotype as determined by FluoroJade positivity, TUNEL assay and Sholl analysis [17, 18]. These data strengthen the concept that immature neurons are more sensitive to insults compared to more differentiated ones [51] and that bilirubin affects survival of neuronal precursors by impairing their neurogenesis, arborization and synaptic connectivity [17, 52]. …”
Section: Discussionsupporting
confidence: 56%
“…In particular, we have previously demonstrated that PCs showed a neurodegenerative phenotype as determined by FluoroJade positivity, TUNEL assay and Sholl analysis [17, 18]. These data strengthen the concept that immature neurons are more sensitive to insults compared to more differentiated ones [51] and that bilirubin affects survival of neuronal precursors by impairing their neurogenesis, arborization and synaptic connectivity [17, 52]. …”
Section: Discussionsupporting
confidence: 56%
“…Moreover, they observed that a compromised motor/co-ordination function occurred when implementation of phototherapy was delayed. Similar alterations in neuronal/axonal unit involving decreased number of dendritic and axonal branches, smaller growth cone area, and reduced dendritic spines and synapses, were previously observed in immature neurons exposed to UCB [21]. Interestingly, treatment with glycoursodeoxycholic acid has shown several neuroprotective properties and no noticeable secondary effect, and the anti-inflammatory interleukin (IL)-10 prevented such reduction in neuritic arborization by UCB [22].…”
Section: Introductionsupporting
confidence: 57%
“…Exposure of neurons to bilirubin results in increased oxidative stress and decreased neuronal proliferation [18,19] and presynaptic neurodegeneration at central glutaminergic synapses [20]. Furthermore, bilirubin administration results in smaller spiral ganglion cell bodies, with decreased cellular density and selective loss of large cranial nerve VIII myelinated fibers [21,22].…”
Section: Introductionmentioning
confidence: 99%